Behavioral change readiness among obese adolescents in Jakarta, Indonesia (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Prochaska’s transtheoretical model of behavioral change process, consisting of stages and processes of change, should be monitored to evaluate obesity management, particularly in adolescents. Two of four processes of change are supporting relationships, which promote behavioral change, and weight management actions, which are activities that push individuals to a particular direction in patients’ weight loss progress. This study aimed to determine the participants’ current stages of change, nutritional status, and their relationship with the processes of change. METHODS This cross-sectional study used secondary data collected in 2018 from 115 obese adolescents aged 15–21 years in Jakarta, Indonesia, using an Indonesian-translated and validated questionnaire adapted from Andrés et al’s study. The questionnaire evaluated participants’ processes of change, focusing on scores of supporting relationships (5 items) and weight management actions (10 items). RESULTS Of the participants, 71.3% were classified as obese grade I, and 28.7% were obese grade II. Most participants were in the contemplation (31.3%) and action (31.3%) stages. The mean supporting relationships and weight management actions scores were different between participants with obese I and obese II (66.67 versus 80, p = 0.004; 64.17 versus 70, p = 0.008, respectively). Meanwhile, no differences were identified in supporting relationships and weight management actions scores in all stages of change. CONCLUSIONS Adolescents with obesity and higher BMI (based on the obesity grading of the WHO Asia Pacific) tended to have significantly higher scores for supporting relationships and weight management actions, indicating that external reinforcement and immediate weight loss actions played pivotal roles in readiness for behavioral change.